Enhanced Early Childhood Placement Program to Facilitate Family Involvement for Future Teachers - Katherine Bussey (Social Sciences)
Navigating family involvement is commonly a cause of concern for pre-service teachers who will soon be early childhood teacher graduates in Australia. This paper uses a Research by Design methodology to analyse the interview and focus group data from 108 pre-service and 135 mentor teachers involved in an enhanced early childhood professional placement partnerships program. This program was used to advance professional relationships through shared professional learning and making time for collegial discussions. The findings show that the program interventions have enabled pre-service teachers to focus on family involvement while on placements, with some sharing their own documentation of children’s learning directly with families.